Reaching consensus on a 'vegetables first' approach to complementary feeding. Issue 3 (September 2016) - Chambers, L.; Hetherington, M.; Cooke, L.; Coulthard, H.; Fewtrell, M.; Emmett, P.; Lowdon, J.; Blissett, J.; Lanigan, J.; Baseley, C.; Stanner, S.
Abstract: On 5 May 2016, the British Nutrition Foundation (BNF) invited leading infant feeding experts to discuss and debate the strength of the evidence base on a 'vegetables first' approach to complementary feeding. Consensus was reached on the translation of the science into practical messages for parents/carers. In particular, it is known that familiarising infants with a variety of vegetables from the start of complementary feeding increases the likelihood that vegetables will be accepted throughout childhood, though currently in the UK vegetables tend not to be prioritised as first foods. Infant feeding guidance could include recommendations to offer tastes of a variety of vegetables when complementary feeding begins, as a first step in the transition from milk to solid foods, so that liking and acceptance are established during this early window of opportunity. This report describes the main themes emerging from the discussions and the specific messaging recommendations which could be included within infant feeding guidance.